Linked labor histories : New England, Colombia, and the making of a global working class - Chomsky, Aviva, 1957- (American encounters/global interactions., 2008)
Exploring globalization from a labor history perspective, Aviva Chomsky provides historically grounded analyses of migration, labor-management collaboration, and the mobility of capital. She illuminates the dynamics of these movements through case studies set mostly in New England and Colombia. Taken together, the case studies offer an intricate portrait of two regions, their industries and workers, and the myriad links between them over the long twentieth century, as well as a new way to conceptualize globalization as a long-term process.